The combination of resonance Raman spectroscopy, optical tweezers and microfluidic systems applied to the study of various heme-containing single cells. Issue 4 (2008) - Ramser Ramser, K. K.; Wenseleers Wenseleers, W. W.; Dewilde Dewilde, S. S.; Doorslaer Doorslaer, S. Van S. Van; Moens Moens, L. L.
Abstract : Several recent studies on the function of neuroglobin (Ngb), a hemoprotein predominantly expressed in the brain, point toward a neuro-protective role during hypoxic-ischemic injuries. The exact mechanism by which Ngb protects the cell against H2 O2 -induced cell death remains to be elucidated. Hence, new tools need to be developed in order to study the protein in vivo or under physiological conditions. In this summary of our work, we demonstrate how resonance Raman spectroscopy, optical tweezers and microfluidic systems were combined to mimic in vivo conditions in an in vitro milieu. The setup has been tested on several globin-containing cells: hemoglobin (Hb) within single red blood cells (RBCs), a nerve globin present in the nerve cord of the annelid Aphrodite aculeata ( A. aculeata ), and wild-type (wt) human neuroglobin (NGB) overexpressed in Escherichia coli ( E. coli ) bacteria. The feasibility of the setup regarding sensitivity and photo-induced effects and the results regarding the oxygen uptake and release will be discussed and compared for each system. The summary of the results show that the method is promising and the setup will be developed further to monitor the dependence of the neuronal action potential on nerve globins.